Encapsulation of Lidocaine nanoparticles in Gadus morhua derived lipoic acid - Vidusha Anand; Ramya Ramadoss; Bargavi Purushothaman; Sandhya Sundar; Suganya Panneer Selvam; Pratibha Ramani; Vanaja Krishna Naik (Elsevier, 2023)
Local Anesthetics are used clinically for anesthesia and analgesia either following surgery or for management of acute and chronic pain conditions. Liposomal Encapsulation aids in improved delivery at the tissue level. This paper deals with formulation and characterization of Gadus morhua derived liposome encapsulated Lidocaine nanoparticles. Materials and methods: Water Soluble liposomes were synthesized and encapsulated to lidocaine. The prepared liposomes were assessed using field emission scanning electron microscope, TEM, FTIR, Zetapotential, Anti-inflammatory property and Drug release kinetics. Results: The structural and morphological characters of the conjugated liposomes were studied using SEM & TEM, surface charge Zetapotential. The cumulative drug release was studied for up to 72 h in which more than 70 % of the drug was released from the Liposomal nanoparticles. FTIR revealed similar functional groups like the control. Stability of the drug was superior than the control. Conclusion: Liposomal conjugation delays the drug release which can be used in slow release applications. Improving the drug release kinetics can be advantageous in many chronic pain conditions. Additionally, the changes in the functional groups can also aid in reduction or masking of bitterness.